Standardized practice design with electronic support mechanisms for surgical process improvement: reducing mechanical ventilation time - Cook, David J; Pulido, Juan N; Thompson, Jeffrey E; Dearani, Joseph A; Ritter, Matthew J; Hanson, Andrew C; Borah, Bijan J; Habermann, Elizabeth B (Annals of surgery, 2014)
Hospital surgical care is complex and subject to unwarranted variation. As part of a multiyear effort, we sought to reduce variability in intraoperative care and management of mechanical ventilation in cardiac surgery. We identified a patient population whose care could be standardized and implemented a protocol-based practice model reinforced by electronic mechanisms. In a large cardiac surgery practice, we built a standardized practice model between 2009 and 2011. We compared mechanical ventilation time before (2008) and after (2012) implementation. To ensure groups were comparable, propensity analysis matched patients from the 2 operative years. In 2012, more than 50% of all cardiac surgical patients were managed with our standardized care model; of those, 769 were one-to-one matched with patients undergoing surgery in 2008. Patients had a mix of coronary artery bypass grafting, valve surgery, and combined procedures. Our practice model reduced median mechanical ventilation duration from 9.3 to 6.3 hours (2008 and 2012) (P < 0.001) and intensive care unit length of stay from 26.3 to 22.5 hours (P < 0.001). Reintubation and intensive care unit readmission were unchanged. Variability in ventilation time was also reduced. We demonstrate that in more than 50% of all cardiac surgical patients, a standardized practice model can be used to achieve better results. Clinical outcomes are improved and unwarranted variability is reduced. Success is driven by clear patient identification and well-defined protocols that are clearly communicated both by electronic tools and by empowerment of bedside providers to advance care when clinical criteria are met.